Saluran Pemasaran Dalam Memasarkan Produk Asuransi - Rendi Prayoga; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
Marketing channels carry out the work of moving products from producers (insurance companies) to consumers/customers. It can overcome the time, place, and ownership gaps that separate products and services from those who need and want them. In practice, this marketing channel must also have product marketing channel management in accordance with OJK regulations. As well as any conflicts that occur in the marketing channel in marketing insurance products. Therefore, the purpose of this article is to provide an explanation of the marketing channels in detail in marketing insurance products to the general public.